Perencanaan Penanganan Kawasan Permukiman Kumuh (Studi Penentuan Kawasan Prioritas untuk Peningkatan Kualitas Infrastruktur pada Kawasan Pemukiman Kumuh di Kota Malang) - Wijaya, Donny Wahyu (Jurnal Ilmiah Administrasi Publik, 2016)
Regions urban slums emerge as one of the impact of the lack of success of development in urban settlements and urban land constraints. This study aims is to identify the characteristics of a slum area, determine the priority areas for improving the quality of infrastructure in the slum areas, and provide recommendations on the strategy of improving the quality of infrastructure slum areas in Malang Municipal. The results showed that based on the assessment of the areas where research was conducted, there are 11 (eleven) classification of slum areas and five (5) priority areas for improving the quality of infrastructure in slum areas. From the result of the SWOT analysis, the recommendation strategy for improving the quality of infrastructure in the slum areas, are: planning improvement of the quality of infrastructure in the slum areas in a comprehensive manner; improve the coordination and synchronization of programs and activities; involve the community in the planning process; improve coordination and synergies with relevant institutions in the spatial use in the city area along in the border areas and riverbanks; increase socialization as an effort to increase understanding and awareness for the public; and to seek opportunities for cooperation with the private sector in improving the quality of infrastructure of the slums.